PERAN PENDIDIKAN AGAMA KRISTEN DALAM KELUARGA TERHADAP PEMBENTUKAN MENTAL, SPIRITUAL DAN KARAKTER ANAK - Lifrani Sakke; Jellistari; Grace; Intan Mentaruk; Alberth Rivaldho (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to examine the role of Christian Religious Education in the family in shaping the mental, spiritual, and character development of children. The family is the first and primary environment in a child’s educational process, including in instilling Christian faith values. Through guidance, teaching, and the example set by parents, children are introduced to spiritual values that serve as the foundation for shaping their mindset, attitudes, and behavior in daily life. Faith education carried out within the family helps children know God, understand His Word, and develop a healthy spiritual life from an early age. This research uses a literature study method by reviewing various relevant sources such as books, scientific journals, and theological references related to Christian Religious Education and character formation in children. The results of the study indicate that the role of parents as educators of faith is very important in shaping the mental, spiritual, and character development of children. Christian values such as love, honesty, humility, faithfulness, and concern for others can be instilled through habituation, teaching, and parental example in family life. Therefore, Christian Religious Education within the family has a significant contribution in forming children who are faithful, possess good character, and are able to apply Christian values in their social life.